PKL Student Knowledge of Common Abbreviations in Recipes at Mandiri YPPM Pharmacy Academy - Verawati; Ria Ceriana; Hanandyo Dardjito (International Journal of Scientific Multidisciplinary Research, 2023)
Medication error is a medical error that can lead to failure in the treatment process. Medication errors can be caused by various factors. One of the factors that influence medication errors is errors in reading prescriptions. One of the important components contained in a recipe is a common abbreviation. Therefore, it is necessary to conduct research to determine the level of knowledge of PKL students at the YPPM Mandiri Pharmacy Academy on common abbreviations in recipes. This research method is through a descriptive approach using a questionnaire as an instrument. The results of this study indicate that the knowledge of PKL students at the YPPM Mandiri Pharmacy Academy categorized as good because 12 questions achieved a score above 70%. However, it is still necessary to increase knowledge so that the value reaches 100% so as to avoid medication errors in the future